2013
DOI: 10.1259/dmfr.20120346
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of imaging methods for detection of bone tissue invasion in patients with oral squamous cell carcinoma

Abstract: The objective of this review is to evaluate the diagnostic accuracy of imaging methods for detection of mandibular bone tissue invasion by squamous cell carcinoma (SCC). A systematic review was carried out of studies in MEDLINE, SciELO and ScienceDirect, published between 1960 and, in English, Spanish or German, which compared detection of mandibular bone tissue invasion via different imaging tests against a histopathology reference standard. Sensitivity and specificity data were extracted from each study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 36 publications
3
41
1
3
Order By: Relevance
“…Kolk et al posit that the combination of CT/SPECT can improve sensitivity and specificity of detecting bony disease, ultimately decreasing false negative and false positive findings that can be associated with conventional CT and MRI imaging . Indeed, a systematic review by Uribe et al in 2013 looked at 5 studies and 130 tumors and concluded that CT and MRI demonstrated the greatest sensitivity (94% and 91%, respectively) and specificity (100%) in detecting mandibular invasion compared with CBCT (83% and 97%, respectively) PET/CT (53% and 97%, respectively), and panoramic X‐ray (55% and 92%, respectively). Other studies demonstrate that an MRI and a bone scan can overestimate mandibular involvement (with more false‐positive results), and that CT, panorex, and clinical examination are the optimal means by which to assess bone invasion …”
Section: Introductionmentioning
confidence: 99%
“…Kolk et al posit that the combination of CT/SPECT can improve sensitivity and specificity of detecting bony disease, ultimately decreasing false negative and false positive findings that can be associated with conventional CT and MRI imaging . Indeed, a systematic review by Uribe et al in 2013 looked at 5 studies and 130 tumors and concluded that CT and MRI demonstrated the greatest sensitivity (94% and 91%, respectively) and specificity (100%) in detecting mandibular invasion compared with CBCT (83% and 97%, respectively) PET/CT (53% and 97%, respectively), and panoramic X‐ray (55% and 92%, respectively). Other studies demonstrate that an MRI and a bone scan can overestimate mandibular involvement (with more false‐positive results), and that CT, panorex, and clinical examination are the optimal means by which to assess bone invasion …”
Section: Introductionmentioning
confidence: 99%
“…Multislice CT and MRI are currently the most widely accepted imaging modalities for staging oral cavity cancer and determining bony invasion . Less utilized imaging modalities include panoramic radiography, single photon emission CT and positron emission tomography . To date, no single or combined evaluation modality has proven to be completely accurate as judged by pathology specimen reports …”
Section: Introductionmentioning
confidence: 99%
“…3 Less utilized imaging modalities include panoramic radiography, single photon emission CT and positron emission tomography. 4 To date, no single or combined evaluation modality has proven to be completely accurate as judged by pathology specimen reports. [1][2][3][4][5] Cone-beam CT (CBCT) is a relatively new imaging modality that utilizes a cone shaped X-ray beam to capture a 3D image in one sweep.…”
Section: Introductionmentioning
confidence: 99%
“…Primer tümörün değerlendirilmesinde, lezyon sınırlarının, prevertebral boşluk infiltrasyonunun belirlenmesinde, kafa tabanına yakın veya intrakraniyal uzanım gösteren tümörlerin değerlendirilmesinde, derin dil kaslarına invazyon varlığının saptanmasında PET/MR, MR komponentinin yüksek yumuşak doku kontrastı nedeniyle PET/BT'den daha iyi tanısal performans gösterir. BT'nin ise özellikle primer tümörün kemik korteksine invazyonunu göstermede MR'dan üstün olabileceği belirtilmiştir (34).…”
Section: Başveboyuntümörlerindepet/mrunclassified